A de-noising scheme for enhancing wavelet-based power quality monitoring system. - Hong-Tzer Yang (IEEE Transactions on power delivery)
By means of the wavelet transform (WT), a power quality (PQ) monitoring system could easily and correctly detect and localize the disturbances in the power systems. However, the signal under investigation is often corrupted by noises, especially the ones with overlapping high-frequency spectrum of the transient signals. The performance of the WT in detecting the disturbance would be greatly degraded, due to the difficulty of distinguishing the noises and the disturbances. To enhance the capability of the WT-based PQ monitoring system, this paper proposes a de-noising approach to detection of transient disturbances in a noisy environment. In the proposed de-noising approach, a threshold of eliminating the influences of noises is determined adaptively according to the background noises. The abilities of the WT in detecting and localizing the disturbances can hence be restored. To test the effectiveness of the developed de-noising scheme, employed were diverse data obtained from the EMTP/ATP programs for the main transient disturbances in the power systems as well as from actual field tests. Using the approach proposed in this paper, remarkable efficiency of monitoring the PQ problems and high tolerance to the noises are approved